A military garrison or cultural mixing pot? Renewed investigations at Shichengzi, a Han Dynasty settlement in Xinjiang. (February 2020) - Sheng, Pengfei; Storozum, Michael J.; Tian, Xiaohong; Wu, Yong
Abstract: Abstract : Excavations at Shichengzi, the probable location of ancient Shule, have revealed diverse burial practices suggesting a population with varied cultural backgrounds. Together with archaeobotanical evidence, this indicates a community of agro-pastoralists and Han Dynasty migrants using diverse cropping patterns to attain self-sufficiency. The project raises interesting questions about the impact of migrations on the identities of inhabitants.